The unveiled face of IEI: Children Cancer Hospital—Egypt (CCHE-57357) experience - Radwan, Nesrine; Medany, Youssef; Rashad, Hanaa; Elhemaly, Ahmed; Hammad, Mahmoud; Rahman, Hany Abdel; Fakhry, Mona; Marouf, Nora Mahmmoud; Mahdy, Ahmed; Elsherif, Mariam; Salama, Maram Farouk; Ali, Nesreen; et al. (Frontiers in Immunology, 2025)
BackgroundInborn errors of immunity (IEI) are a heterogeneous group of different disorders characterized by a defect in the function and/or components of the immune system. Malignancy is the second common cause of death following recurrent infections.AimWe present our experience in Children Cancer Hospital Egypt (CCHE-57357) in diagnosing IEI patients who first presented with malignancy rather than infections.MethodsData of 19 IEI patients with malignancy referred to the immunology clinic was collected. The reasons for referral were stunted growth or presence of bronchiectasis at presentation, persistent eczema, significant chemotoxicity, history of recurrent infection either during or after stoppage of chemotherapy, and relapse of lymphoid malignancy after auto-BMT.ResultsThe patients comprised 14/5 men/women. Their median age at diagnosis with malignancy was 7 years (1.5–16 years). In addition, 13/19 had lymphoma (Hodgkin’s/non-Hodgkin’s) and 6/19 patients had leukemia. Moreover, 9/19 had history of repeated infections, 4/19 had failure to thrive, 5/19 had clubbing, 4/19 had bronchiectasis, 3/19 had significant chemotoxicity, 8/19 had low immunoglobulin, 12/19 had abnormal lymphocyte subsets, and 3/19 had a relapse of the original disease. Genetic testing was done to 18/19. The diagnoses based on genetic and/or immunological investigation according to the IUIS classification were 7/19 (37%) immune-dysregulation, 4/19 (21%) combined immunodeficiency with syndromic features, 3/19 (15.7%), combined immunodeficiency, 3/19 (15.7%) predominantly antibody defect, and 2/19 (10.5%) bone marrow failure defect.ConclusionCollaborative work between immunologist and oncologist helped in diagnosing patients with IEI who first presented with malignancy.